Scaling Logic Area With Multitier Standard Cells - Florian Freye; Christian Lanius; Hossein Hashemi Shadmehri; Diana Gohringer; Tobias Gemmeke (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
While the footprint of digital complementary metal-oxide–semiconductor (CMOS) circuits has continued to decrease over the years, physical limitations for further intralayer geometric scaling become apparent. To further increase the logic density, the international roadmap for devices and systems (IRDS) predicts a transition from a single layer of transistors per die to monolithically stacking transistors in multiple tiers starting in 2031. This raises the question of the extent to which these can be exploited in 3-D standard cells to improve logic density. In this work, we investigate the scaling potential of realizing standard cells employing two or three dedicated tiers. For this, specific multitier virtual physical design kits are derived based on the open ASAP7. A typical RISC-V implementation realized in a classic standard cell library is used to identify the subset of the most relevant standard cells. In accordance with the virtual physical design kit (PDK), 3-D derivatives of the single-tier standard cells are crafted and evaluated with respect to achievable logic density considering standard synthesis benchmarks and blocks on the architecture level.